2016
DOI: 10.1016/j.trsl.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease: exploring gut pathophysiology for novel therapeutic targets

Abstract: Ulcerative colitis and Crohn's disease are the 2 major phenotypes of inflammatory bowel disease (IBD), which are influenced by a complex interplay of immunological and genetic elements, though the precise etiology still remains unknown. With IBD developing into a globally prevailing disease, there is a need to explore new targets and a thorough understanding of the pathophysiological differences between the healthy and diseased gut could unearth new therapeutic opportunities. In this review, we provide an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 243 publications
0
90
0
5
Order By: Relevance
“…Although the precise etiology of IBD remains unknown [1] , it is mainly caused by ulcerative colitis and Crohn's disease [2] . Crohn's disease causes inflammation that extends through the entire bowel wall, whereas ulcerative colitis affects the colon and/or the large intestine [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise etiology of IBD remains unknown [1] , it is mainly caused by ulcerative colitis and Crohn's disease [2] . Crohn's disease causes inflammation that extends through the entire bowel wall, whereas ulcerative colitis affects the colon and/or the large intestine [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identification of genetic factors associated with IBD will aid in the development of novel therapeutic targets [37]. Genome-wide association studies (GWAS) have found more than 200 genetic risk loci for IBD [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Among these pro-inflammatory mediators, the pro-inflammatory cytokines, particularly tumor necrosis factor α (TNF-α), interleukin (IL)-1β, IL-6, IL-12 and IL-23 are believed to play crucial roles in the pathogenesis of IBD [79]. Therefore,the regulation of these cytokines has been proposed as a strategy to treat IBD [10]. In this regard, anti-inflammatory drugs, aminosalicylates and corticosteroids, and immunosuppressive agents, are considered as the first-line therapies for IBD patients [11].…”
Section: Introductionmentioning
confidence: 99%